Annealing time dependence in the fabrication of Bismuth-based Perovskite solar cells (Bi-PeSCs) by the hot immersion method / M. F. Achoi S. Kato, N. Kishi, T. Soga - Achoi, M. F.; S., Kato; N., Kishi; T., Soga (Faculty of Mechanical Engineering Universiti Teknologi MARA (UiTM), 2024)
Lead-free perovskite solar cells have attracted attention as an environmentally friendly future energy source. However, their performance is still low at present due to the poor morphology of the film and the complicated process of fabrication. The annealing period, as a key parameter, has been identified to control the morphology of MA3Bi2I9 (MBI) perovskite film fabricated by the Hot Immersion Method (HIM) with the annealing period varying between 5 to 25 minutes. SEM images visually depicted that a longer period of annealing induced perovskite film to form a larger crystallite size with a compact film, resulting in a rougher surface. The MBI films fabricated at 25 minutes showed a high crystallinity of films and exhibited a high absorption with a longer absorption wavelength and a narrow bandgap, leading to enhanced solar cell performance. By optimizing the annealing time, the efficiency of the device has been enhanced almost eight times compared to a shorter period of annealing. Our findings suggest that the compact MBI films can be obtained by using this simple method (HIM), and yet the performance of solar cell devices can be achieved, thus providing another alternative way to fabricate MBI-based perovskite solar cells (PeSC’s) in the future